The Histopathologic Features of Sickle Cell Hepatopathy: A Multi-Institutional Study. Issue 1 (31st August 2021) - Saeed, Omer; Panarelli, Nicole; Umrau, Kavita; Lee, Hwajeong; Westerhoff, Maria; Cheng, Jerome; Lin, Jingmei
Abstract: Objectives: Recent data on hepatic histopathology in patients with sickle cell disease (SCD) are lacking. Methods: A total of 39 liver biopsies from SCD patients from 4 medical institutes were systematically evaluated. Results: The average age of patients was 27 years; 23 were female. The majority of the patients had hemoglobin SS (33), 3 had hemoglobin SC, and 3 sickle cell trait. Elevated liver functional tests and evaluation for cirrhosis were the main indications for biopsy. At the time of biopsy, most had elevated liver transaminases or hepatomegaly. The most common histopathologic abnormalities were Kupffer cell erythrophagocytosis (76.9%), hemosiderosis (74.4%), sinusoidal dilatation (71.8%), and intrasinusoidal sickled red cells (69.3%). Portal inflammation, lobular inflammation, and bile duct injury were mild to minimal and present in a minority of cases. Advanced fibrosis was present in 28.2% of the cases. Conclusions: The typical histopathologic features seen in patients with SCD include Kupffer cell erythrophagocytosis, hemosiderosis, sinusoidal dilatation, and intrasinusoidal sickled red cells in a pauci-inflammatory or uninflamed background. Necrosis is less common than reported in older literature. Pathologists should be aware that significant portal and lobular inflammation, interface activity, and bile duct injury are unusual and may be suggestive of other etiologies.